Ego complexities - Špoljarić, Bernard (Array, 2020)
The research on the complexities of ego has its starting point in the self, understood as a complex concept, superior to the diagnostic constructs that tend to perform the medical-qualitative evaluation of each self. Besides explaining the notion, the aim is to emphasise the clear distinction between egoism and narcissism, with narcissism being merely one of the possible modes and explanations of self, i.e. general and universal domain of subjectivity. Complexities primarily indicate the unsolved intricacy of ego, together with the associated concepts of subjectivity and individuality. The outline of the general model of the ego, its constitution and operability, provides a possible common basis for a therapeutic, philosophical and moral understanding of aporias related to the psychopathological states present in the seemingly emancipated complete individual.